A Sunscreen Based on Avobenzone Loaded in Solid Lipid Nanoparticles for Enhanced Sun Protection - Natarajan, Jawahar; Krishnan, Pavalan; Arokianathan, Sebatini Sinsi; Sivakumar, Sharuni; Saravanan, Parish Vendar; Rao, Roshan Prasad (International Journal of Pharmaceutical Investigation, 2025)
Objectives Sunscreen cosmeceuticals play a crucial role in protecting the skin from dangerous ultraviolet radiation, which is linked to various dermatological diseases and skin cancers. Avobenzone is extensively used organic ultraviolet ray gauze; however, due to its inherent instability and limited skin penetration, it has led to research into developing novel delivery systems. This study introduces a pioneering sunscreen formulation employing avobenzone incorporated in solid lipid nanoparticles to enhance sun protection efficacy. Materials and Methods The solid lipid nanoparticles were prepared by the microemulsion method by using glycerol monostearate, soya lecithin, avobenzone and Pluronic F127, which results in the formulation of nano-emulsion and the subsequent formation of solid lipid nanoparticles by lipid precipitation and the sunscreen is loaded in the solid lipid nanoparticles by mixing both the oil phase (cetyl alcohol, cocoa butter) and the aqueous phase (triethanolamine, water) together until a cream-like consistency is obtained. This formulation was then characterized for particle size, zeta potential, entrapment efficiency, sun protection factor determination, microbial studies and photostability studies. Results The results indicate a reduction of avobenzone concentrations with a decrease in particle size and show good entrapment efficiency as well as, an ideal sun protection factor range for better ultraviolet absorption, validating the potential of solid lipid nanoparticles-based delivery. Moreover, the microbial studies and photostability assessments demonstrated the safety and biocompatibility of the developed sunscreens. Conclusion This new sunscreen cosmeceutical offers a promising avenue for effective ultra violet protection and encourages further exploration of solid lipid nanoparticles in sunscreen enhancement.
Keywords: Sunscreen; Ultraviolet Radiation; Avobenzone; Solid-Lipid Nano Particle; Microemulsion